Reklámok hatása a fogyasztókra. - Horváth Zsuzsanna (2015)
The impressions of the present modern consumer society are continuously growing. The flow of information affects all; we can feel the effect of influence, and the good and bad effects of information. Advertisements is one of marketing communication devices that they were here before time and since that they are everywhere in the society. These adver-tisements have good and bad effect, too, but the society can decide that this effect is good or bad. Advertisements can be value, because they give us information’s and these infor-mation’s are value for us. In our world, when we see more and more medias day to day the advertising professionals have to know a lot of different creative methods how to attract the attention of consumers. In my thesis I would described the applications of these creative devices, and their effect on the consumers. I have a hypothesis, that internet is more and more famous, but the con-sumers can be influenced more the advertisements on the television or the print advertis-ing. I suppose that we can reach more purchasing power with different pictures and crea-tive, colourful advertisements. However, I think that the quality and the use of product is not the most important feature for us in this modern society, the most important aspect of choosing a product is the design of the package and the product. I describe my statements in the first part of my thesis with secondary researches, in the second part of the thesis I expound a survey primary research. In my thesis I investigate, what kind of Medias what kind of impacts are on costumers. I study there are different forms, different colours and signs, which are different effects on costumers. I would describe that society decide how advertisements can influence people, but people know that advertisement is the most im-portant by purchasing and I think it is a brave saying but without advertisements we could not live.